THE EFFECTIVENESS OF RHIZOBACTERIA AS BIOPROTECTANTS TO MITIGATE FUSARIUM WILT DISEASE AND AS BIOSTIMULANTS TO IMPROVE THE GROWTH OF CHILI (Capsicum annuum) - Khalimi, Khamdan; Alit Susanta Wirya, Gusti Ngurah; Wirya Suputra, I Putu; Citra Innosensia, Ni Luh Putu (International Journal of Biosciences and Biotechnology; Vol 10 No 1 (2022): INTERNATIONAL JOURNAL OF BIOSCIENCES AND BIOTECHNOLOGY, 2022)
The aims of this study were to examine the potential of Rhizobacteria as bioprotectants and biostimulants on chili. The potential as bioprotectants was tested by the ability of these Rhizobacteria to inhibit the growth of the pathogenic fungus Fusarium oxysporum f.sp. capsici in vitro. Moreover, as biostimulants was tested by the ability of these rhizobacteria to produce IAA compounds and their ability to increase the plant growth parameter of chili. Four rhizobacteria were challenged for antagonistic activity against F. oxysporum f.sp . capsici. Chili seeds in this experiment were soaked in four different Rhizobacteria suspension for 15 minutes. For control, seeds were soaked with sterile water instead of Rhizobacteria suspension. Results of this experiment showed that four isolates of Rhizobacteria showed strong inhibitory activity against F. oxysporum f.sp. capsici on PDA medium. Percentage of inhibitory activity varied from 77,33% to 89,79%. The application of four isolates recorded significantly increased the plant growth parameters of chili. The plant height, number of leaves, leaf area, root length, shoot dry mass, root dry mass, and chlorophyll content on treated plants significantly higher than those of untreated control plants according to the Duncan’s multiple range test (P<0.05%). These results indicate that the tested Rhizobacteria can be used as bioprotectants because they can inhibit the growth of F. oxysporum f.sp. capsici and simultaneously as a biostimulant for the ability to produce IAA compounds and stimulate the growth of chili.